Disaster control practices among library staff in Federal University Libraries in North East, Nigeria - Abdullahi, Suleiman; Dewa, Abdullahi A.; Musa, Abdulaziz; Kobi, Haruna Garba (Communicate: Journal of Library and Information Science, 2025)
This study examined Disaster control practices among library staff in federal universities in North East, Nigeria. Four research questions guided the study. Four hypotheses were formulated and tested at 0.05 level of significance. The design of the study was descriptive survey research. The population of the study comprised of 345 Professional and Para-professional library staff in federal university libraries in North East, Nigeria. The sample population of the study was the entire population as it was considered manageable in size. Questionnaire and observation checklist were the instruments employed for data collection. A total of 217(62.9%) of the questionnaire were retrieved. Data collected was analysed using frequency, mean and standard deviation to answer the research questions. The t-test statistics was used in testing the hypotheses at (p<0.05) level of significance. Data collected from the interview were analysed qualitatively. The study recommended the need for federal university libraries to create periodic awareness forum for both the library staff and users on matters relating to disaster and preventive steps and regular training programs should be organized to enhance disaster control practices in libraries of the federal universities in North East, Nigeria.